Clinical outcome of maintenance electroconvulsive therapy in comorbid Posttraumatic Stress Disorder and major depressive disorder. (October 2018) - Ahmadi, Naser; Moss, Lori; Hauser, Peter; Nemeroff, Charles; Atre-Vaidya, Nutan
Abstract: Background: Post-traumatic stress disorder (PTSD) and major depressive disorder (MDD) are prevalent and frequently comorbid. Approximately 42–48% of patients with PTSD also meet diagnostic criteria for MDD. Maintenance electroconvulsive therapy (mECT) has been found to be efficacious for the prevention of recurrence of MDD. This study investigated the efficacy of mECT in the treatment of MDD with and without comorbid syndromal PTSD. Methods: This retrospective study includes 36 patients, 26 with MDD and 10 with comorbid MDD & PTSD receiving monthly mECT for a mean of 1.5 years. The mean age was 52 ± 14 years and 25% were female. The change in PTSD and MDD symptoms in response to mECT was assessed using Clinical Global Impression - Severity Scale (CGI-S). Heart rate variability (HRV), 12-month hospitalization rate, suicide rate and all-cause mortality in response to mECT were assessed and compared between groups using repeated generalized linear regression (GLM) analysis. Results: At mECT baseline, there were no statistically significant differences in CGI-S scores, HRV between patients with MDD alone and those with comorbid MDD and PTSD (P > 0.05). After 12-months of mECT, a significant increase in HRV (mean difference: 10.9 95%CI 4.8–20.3, p = 0.001) and decrease in CGI-S overall (mean difference: 3.5, 95% CI 3.3–3.6, p = 0.001)], PTSD (mean difference: 3.4, 95% CI 3.2–3.6, p = 0.001)], and MDD (mean difference: 3.8, 95% CI 3.5–3.9, p = 0.001)] symptoms in both groups were noted (p < 0.05). No psychiatric hospitalization or suicide occurred in any of the patients. Conclusions: Maintenance ECT is associated with improved HRV, reduction of both major depression and PTSD symptoms, and a favorable clinical outcome.